That working-class ethic … where there’s a will there’s a way”: A strengths-based approach to developing employable scholars - O'Shea, Sarah; Delahunty, Janine (2019)
Universities across the globe are ‘opening wide’ the doors of academe and students from increasingly diverse backgrounds are responding in their thousands. Despite the resulting increase in both student numbers and student diversity, particularly those who are the first in their families to attend university, many institutional support models continue to focus on how to ‘fill–up’ these learners with the requisite skills needed to succeed at university. However, such an approach implicitly assumes that the knowledges derived from a lived experience that does not include a family tradition of university attendance, is somehow at odds with achieving ‘success’ at university and, ultimately, employment after graduation. This chapter proposes an alternative strengths-based perspective that explores the capabilities and capitals that learners bring with them to the HE environment in order to counter such assumed deficit framing. By exploring the strengths, skills, knowledge and work ethic of first-generation students, we can begin to move away from the perception of these learners as being somehow ‘lacking’ and equally acknowledge the key role that family and friends may play in supporting them in various ways throughout their studies. Further, in acknowledging the knowledge, skills and experience that these diverse learners bring (including the resilience they likely already hold) this chapter foregrounds how students themselves can navigate this terrain and consider their post-graduation futures.